Predicting the Creative Self-efficacy ‎among High-school Students through ‎Mindfulness - Al-Rababaa, Hamzah; Jabaatah, Bassam (Jordan Journal of Educational Sciences, 2021)
This study aimed to reveal the predictive ability of mindfulness of the creative self-efficacy among a sample of (591) male and female students from the secondary stage in Irbid governorate, chosen using the available sampling method during the first semester of the academic year 2018/2019. To achieve the goals of the study, the creative self-efficacy and the five faces of mindfulness scales were used. The results showed that the levels of high-school students’ creative self-efficacy total score and its sub-domains were high. The results also revealed that the means of males on creative self-efficacy total score and its sub-domains were higher than those of females.The results also showed that the level of mindfulness total score and its sub-domains was moderate, except for the domain of observing which was high. The results also revealed that the means of males on mindfulness total score and sub-domains were higher than for females, and that the means of the students in the professional stream on mindfulness total score and subdomains were higher than those for other streams. Finally, the results showed that the mindfulness total score explained 19.9% of the variance in the creative self-efficacy, while the subdomains of mindfulness explained 39% of this variance